An adiponectin receptor agonist promote osteogenesis via regulating bone‐fat balance. (3rd May 2021) - Liu, Hanghang; Liu, Shibo; Ji, Huanzhong; Zhao, Qiucheng; Liu, Yao; Hu, Pei; Luo, En
Abstract: Objectives: Adiponectin signalling has been considered to be a promising target to treat diabetes‐related osteoporosis. However, contradictory results regarding bone formation were observed due to the various isoforms of adiponectin. Therefore, it would be necessary to investigate the effect of adiponectin receptor signals in regulating bone‐fat balance. Materials and Methods: We primarily applied a newly found specific activator for adiponectin receptor, AdipoRon, to treat bone metabolism‐related cells to investigate the role of Adiponectin receptor signals on bone‐fat balance. We then established femur defect mouse model and treated them with AdipoRon to see whether adiponectin receptor activation could promote bone regeneration. Results: We found that AdipoRon could slightly inhibit the proliferation of pre‐osteoblast and pre‐osteoclast, but AdipoRon showed no effect on the viability of mesenchymal stromal cells. AdipoRon could remarkably promote cell migration of mesenchymal stromal cells. Additionally, AdipoRon promoted osteogenesis in both pre‐osteoblasts and mesenchymal cells. Besides, AdipoRon significantly inhibited osteoclastogenesis via its direct impact on pre‐osteoclast and its indirect inhibition of RANKL in osteoblast. Moreover, mesenchymal stromal stems cells showed obviously decreased adipogenesis when treated with AdipoRon. Consistently, AdipoRon‐treated mice showed faster bone regeneration and repressed adipogenesis. Conclusions: Our study demonstrated a pro‐osteogenic, anti‐adipogenic and anti‐osteoclastogenic effect of adiponectin receptor activation in young mice, which suggested adiponectin receptor signalling was involved in bone regeneration and bone‐fat balance regulation. Abstract : Adiponectin receptors 1 and 2 are expressed early in mesenchymal stem cells lineage and in precursors including pre‐osteoblast, pre‐osteoclasts and chondrocytes. Using an adiponectin receptor agonist AdipoRon, our study demonstrated a pro‐osteogenic, anti‐adipogenic and anti‐osteoclastogenic effect of adiponectin receptor activation in young mice, which suggested adiponectin receptor signalling was involved in bone regeneration and bone‐fat balance regulation.